ISLAMIC IDENTITY IN TURKEY’S ORIENTATIONS TOWARDS THE EUROPEAN UNION 1992-2004 A.D - Hamzah Hussein, Dr. Mohammed; AlawAI-Samarraie, Dr. Ahmed Mahmood; Riyadh Abdul Majeed, Dr. Lubna (The journal of contemporary issues in business and government, 2022)
Turkey’s membership in the European Union is one of the most historical and decisive events in the construction of the social, economic and political structure of Europe. It is clear that Turkey is not a strong candidate like the others. Turkey is challenging the European system in order to be a part of it. Ironically, this challenge is as much cultural as it is political for Europe, which is more and more preoccupied with its identity, its borders, and its future. The opening of membership negotiations has alarmed the Europeans, prompting intense and unprecedented debates within the corridors of the European Parliament. The Muslim Turks, on the threshold of the European Union, are once again being imagined by turning back to Ottoman history and memory. Although EU membership is a political issue. But in the case of Turkey, discussions show that he is beyond politics. It seems that the Europeans are convinced that Turkey is a mirror of the cultural and religious heritage of Europe, and this has sparked an existential reflection on nature and identity thanks to its close interest and active presence at the local and European levels. European Christian churches are among the actors most participating in these discussions in a highly secular Europe Since religion should have nothing to do with politics, what kind of position or role should churches assume? Has religion returned to the new Europe? This paper aims to look at how "Christian Europe", which has historically led the hostile response to Muslim Turks, is now in a position to integrate Muslim Turkey into the European Union.